Experimental verification of spherical-wave effect on the AVO response and implications for three-term inversion - Alhussain, Mohammed; Gurevich, Boris; Urosevic, Milovan (Society of Exploration Geophysics, 2008)
Spherical-wave offset-dependent reflectivity is investigated by measuring ultrasonic reflection amplitudes from a water/Plexiglas interface. The experimental results show substantial deviation of the measured amplitudes from the plane-wave reflection coefficients at large angles. However, full-wave numerical simulations of the point source reflection response using the reflectivity algorithm show excellent agreement with the measurements, demonstrating that the deviation from the plane-wave response is caused by the wavefront curvature. To analyze the effect of wavefront curvature on elastic inversion, we simulate the spherical-wave reflectivity at different frequencies and invert for elastic parameters by least-square fitting of the plane-wave (Zoeppritz) solution. The results show that the two-parameter inversion based on the intercept and gradient is robust, although estimation of three parameters (VP, VS, and density) that use the curvature of the offset variation with angle (AVA) response is prone to substantial frequency-dependent errors. We propose an alternative approach to parameter estimation, one that uses critical angles estimated from AVA curves (instead of the AVA curvature). This approach shows a significant improvement in the estimation of elastic parameters, and it could be applied to class 1 AVO responses